2019
DOI: 10.1038/s41598-019-47491-z
|View full text |Cite
|
Sign up to set email alerts
|

Nano-hydroxyapatite in oral care cosmetics: characterization and cytotoxicity assessment

Abstract: Nano-hydroxyapatite has been used as an oral care ingredient, being incorporated in several products for the treatment of dental hypersensitivity and enamel remineralisation. Despite its promising results, regulatory and safety concerns have been discussed and questioned by the European Scientific Committee on Consumer Safety (SCCS) regarding the usage of hydroxyapatite nanoparticles in oral care products. In this work, a commercially available nano-hydroxyapatite was characterized and its cytocompatibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(49 citation statements)
references
References 31 publications
3
45
0
1
Order By: Relevance
“…Therefore, the relevant properties in the achieved products (toothpaste and mouthwash) are dependent mainly on the nanosized dimension [3,4,12,[27][28][29][30][31][32][33][34]. However, to our knowledge, no studies have focused on NPs ageing or reorganization in relation to their stability in the oral care field.…”
Section: Properties and Structural Features Of Nanosystems (Nanomatermentioning
confidence: 99%
“…Therefore, the relevant properties in the achieved products (toothpaste and mouthwash) are dependent mainly on the nanosized dimension [3,4,12,[27][28][29][30][31][32][33][34]. However, to our knowledge, no studies have focused on NPs ageing or reorganization in relation to their stability in the oral care field.…”
Section: Properties and Structural Features Of Nanosystems (Nanomatermentioning
confidence: 99%
“…The cell metabolic activity, evaluated using the resazurin assay and tested after 1, 3, and 7 days, is represented in Figure 10. This is a very useful test to assess mitochondrial metabolic activity, as the irreversible reaction of resazurin to resorufin is proportional to aerobic respiration [86]. Three types of samples were tested, namely, the 50/50 Coll/CTS, 50/50 SF/Coll, and 50/50 SF/CTS mixtures cross-linked by glyoxal solution, as the samples without cross-linking agent were very quickly dissolved.…”
Section: In Vitro Cytotoxicity Assay-metabolic Activitymentioning
confidence: 99%
“…There were several studies that demonstrated that HA and its related dissolution products could be quite harmless for use in devices, such as, for instance, bone implants [41,42,43]. However, some other studies still considered the potential risks of such materials, mainly due to the addition of other “doping” elements, such as Sr, Zn, etc.…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%